A new generic simulator for the teaching of assembly programming - Camarmas-Alonso, Diego; Garcia-Carballeira, Felix; Del-Pozo-Punal, Elias; Mateos, Alejandro Calderon (2021 XLVII Latin American Computing Conference (CLEI), 2021)
This article introduces CREATOR, a new generic simulator for assembly programming, developed by the ARCOS group at the UC3M. CREATOR is a new, highly intuitive, and portable simulator that runs from a web browser (no installation needed). This simulator comes with the MIPS32 and RISC-V (32IMF) instruction set. Nevertheless, CREATOR allows, from the simulator itself, to edit and define other instruction sets (instructions, format, registers, etc.). Even more, CREATOR allows the definition of the parameter passing convention to be used in the instruction set. Once each particular instruction set (MIPS32, ARM, RISCV, etc.) has been defined, students can use CREATOR to edit, compile, execute and debug programs written in the associated assembler. The simulator also allows checking that the developed programs comply with the parameter passing convention defined for the instruction set. CREATOR lets us create subroutine libraries that can be loaded and linked to other assembly programs developed in the simulator. All CREATOR features allows teacher to design and deploy practical laboratories more adapted to the desired teaching goals. That improves the teaching experience of the assembly language frequently used in different subjects such as Computer Architecture or Computer Structure. The experience of its use has been very positive in the past courses for students and teachers in both the Universidad Carlos III de Madrid (UC3M) and the Universidad Castilla la Mancha (UCLM).